KEBIJAKAN DIVIDEN, INVESTASI, PENDANAAN, KEPEMILIKAN, DAN NILAI PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Rowland Bismark Fernando Pasaribu; Dionysia Kowanda; Citra Wulandari (Jurnal Riset Manajemen dan Bisnis, 2017)
This study aimed to get empirical evidence about the influence of Dividend Policy, InvestmentDecisions, Decisions Funding, Managerial Ownership and Institutional Ownership as theindependent variable on the dependent variable value as a company. This study used a sample usingpurposive sampling techniques in manufacturing companies listed in Indonesia Stock Exchange inLQ45 index period 2008-2013. Total sample of this research is 20 companies. The result of studyproves that simultaneously Dividend Policy, Investment Decisions, Decisions Funding, ManagerialOwnership, and Institutional Ownership has significant effect on company value, while partially onlyInvestment and Financing Decisions that significantly influence the Company Values.Keywords: Dividend Policy, Investment Decisions, Decisions Funding, Managerial Ownership,Institutional Ownership and Corporate Value